FORMING MANAGEMENT IMPACTS IN AVIATION COMPANIES ECONOMIC DEVELOPMENT ADMINISTRATION SYSTEM - Prokhorova, Victoria; Bezuhla, Yuliia (Proceedings of National Aviation University (archive), 2016)
Purpose: Oriented reflective approach to management involves restructuring of goal, ideal and pragmatic, creating a program of action, organizing, correcting, control the definition of the new strategy. This process is only possible with multidimensional analysis and reflection of all the administrative restructuring process and its elements in determining and planning activities, creating conditions of restructuring, predicting outcomes and consequences of making a choice of ways to solve problems means to achieve the goal of information called ' bonds with participants restructuring process and correction flow management process based on continuous reflection. Methods: Development of the system of economic development now requires the use of mechanisms for continuous monitoring of internal and external environment to identify factors that threaten businesses. Rest of this is possible through the use of diagnostic tests: static analysis, expert diagnosis, linear and dynamic programming. Results: Built as part of the study economic and mathematical models can determine the status and level of economic development potential of aerospace companies that were investigated, confirming the need for action to manage economic development. To develop the mechanism of competition in the aircraft building sector must: implementation in practice of management motivation mechanisms to ensure the appropriate level of interest in the functioning of airlines on the basis of private property; formation of economic market institutions in the field of aircraft construction, affecting the creation of a competitive environment. Discussion: Stipulates that in difficult economic crisis positive results can be achieved managers who are constantly looking for original approaches to inclusion in the development process by aligning internal external opportunities generated by market. It is concluded that aviation business management in times of economic instability or crisis requires the development and implementation of (the use of) anti-crisis program managers of higher managerial. Such programs should include a system of economic analysis, forecasting, design and implementation of complex innovative projects.